2016
DOI: 10.1111/geoa.12122
|View full text |Cite
|
Sign up to set email alerts
|

Implications from chemical, structural and mineralogical studies of magnetic microspherules from around the lower younger dryas boundary (new mexico, usa)

Abstract: Hollow magnetic microspherules from along the lower Younger Dryas boundary (c. 12.9 ka bp) in New Mexico (USA) were studied using scanning electron microscopy, electron probe microanalysis, X‐ray diffraction, and laser‐ablation inductively coupled‐plasma mass spectrometry methods. The shell of the microspherules (10–15% of the spherule's diameter) displays dendritic surface textures, which are likely due to quenching during rapid cooling of molten material. Structurally, multiple single‐magnetite crystals atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 89 publications
3
20
0
2
Order By: Relevance
“…Andronikov et al 19. reported that Pt, Ir, and Os values were near detection limits for spherules, and therefore, have high uncertainties.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Andronikov et al 19. reported that Pt, Ir, and Os values were near detection limits for spherules, and therefore, have high uncertainties.…”
mentioning
confidence: 98%
“…Specifically, questions have been raised regarding the nature or replicability of the reported impact proxies, the accuracy of the established chronology, and its purported effects on humans and animals at the YD onset12131415161718. All of these criticisms have been addressed by additional and independent studies replicating the original findings of Firestone et al 371920…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller fragments, such as the near clay size grain in Fig. 8A, with small bulbous protrusions, depict a melted/quenched morphology similar to that described by Andronikov et al, 2016a) suggestive of an airburst origin. The chemistry of this grain and its coating, Ni and Sn in particular, is suggestive of a cosmic impact (De Laeter and Jeffrey, 1965), with a high content of Fe supporting an impact interpretation, although no crater has been conclusively identified yet.…”
Section: Guil/po Catchmentsmentioning
confidence: 53%
“…(), but were not observed in such spherules by Andronikov et al . (). The sample 1PLM1320‐1 from Palominas Arroyo displays trace element patterns that are similar to those in the Murray Springs LYDB sediments, but the features are not as strongly pronounced (Fig.…”
Section: Resultsmentioning
confidence: 97%